Peripatric speciation in an endemic Macaronesian plant after recent divergence from a widespread relative - Valtueña, Francisco J. (PLoS One, 2017)
The Macaronesian Scrophularia lowei is hypothesized to have arisen from the widespread S. arguta on the basis of several phylogenetic studies of the genus, but sampling has been limited. Although these two annual species are morphologically distinct, the origin of S. lowei is unclear because genetic studies focused on this Macaronesian species are lacking. We studied 5 S. lowei and 25 S. arguta populations to determine the relationship of both species and to infer the geographical origin of S. lowei. The timing of S. lowei divergence and differentiation was inferred by dating analysis of the ITS region. A phylogenetic analysis of two nuclear (ITS and ETS) and two chloroplast (psbJ–petA and psbA–trnH) DNA regions was performed to study the relationship between the two species, and genetic differentiation was analysed by AMOVA. Haplotype network construction and Bayesian phylogeographic analysis were conducted using chloroplast DNA regions and a spatial clustering analysis was carried out on a combined dataset of all studied regions. Our results indicate that both species constitute a well-supported clade that diverged in the Miocene and differentiated in the Late Miocene-Pleistocene. Although S. lowei constitutes a well-supported clade according to nDNA, cpDNA revealed a close relationship between S. lowei and western Canarian S. arguta, a finding supported by the spatial clustering analysis. Both species have strong population structure, with most genetic variability explained by inter-population differences. Our study therefore supports a recent peripatric speciation of S. lowei—a taxon that differs morphologically and genetically at the nDNA level from its closest relative, S. arguta, but not according to cpDNA, from the closest Macaronesian populations of that species. In addition, a recent dispersal of S. arguta to Madeira from Canary Islands or Selvagens Islands and a rapid morphological differentiation after the colonization to generate S. lowei is the most likely hypothesis to explain the origin of the last taxon.